2019
DOI: 10.3390/polym11122034
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning on 3D Printed Polymers for Mechanically Stabilized Filter Composites

Abstract: Electrospinning is a frequently used method to prepare air and water filters. Electrospun nanofiber mats can have very small pores, allowing for filtering of even the smallest particles or molecules. In addition, their high surface-to-volume ratio allows for the integration of materials which may additionally treat the filtered material through photo-degradation, possess antimicrobial properties, etc., thus enhancing their applicability. However, the fine nanofiber mats are prone to mechanical damage. Possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…In the FDM printing process, a control model supports the working principle of the entire system, which combines various parameters, namely structural, processing, and extruder-related parameters [ 20 ]. Previous studies have reported that process parameters significantly affect the quality and mechanical properties of FDM-printed parts, such as the printing orientation, layer thickness, feed rate, infill density and pattern, printing speed, and extrusion temperature [ 7 , 8 , 9 , 11 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Several studies [ 8 , 9 , 22 ] have shown that the printing orientation significantly changes the structures of printed parts, resulting in a variation of their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the FDM printing process, a control model supports the working principle of the entire system, which combines various parameters, namely structural, processing, and extruder-related parameters [ 20 ]. Previous studies have reported that process parameters significantly affect the quality and mechanical properties of FDM-printed parts, such as the printing orientation, layer thickness, feed rate, infill density and pattern, printing speed, and extrusion temperature [ 7 , 8 , 9 , 11 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Several studies [ 8 , 9 , 22 ] have shown that the printing orientation significantly changes the structures of printed parts, resulting in a variation of their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…At present, researchers are interested in the application of PLA and its composite materials in the field of 3D printing. Kozior et al prepared electrospinning PAN nanofiber mats on 3D printed scaffolds of rigid PLA, which have application potential in filtration [ 5 ]. Liu et al studied 3D printing scaffolds for bone tissue repairing consisting of poly (L-lactide) (PLLA) matrix [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…To a large extent it is related to the possibility of using three-dimensional models obtained directly from X-rays and computed tomography. At the same time, there are scientific papers being published in which the creation of hybrid solutions is discussed, i.e., printing model based on existing objects, which is widely used in the textile industry [ 6 ], heavy industry [ 7 ] and filtering application [ 8 , 9 ]. Additive manufacturing itself has become a fully valuable field of science, in which new materials, technological parameters, dimensional and shape accuracy of manufactured objects are still being studied, in particular including the technological surface layer.…”
Section: Introductionmentioning
confidence: 99%